Compressed Sensing Based Synthetic Transmit Aperture for Phased Array Using Hadamard Encoded Diverging Wave Transmissions - Liu, Jing; Luo, Jianwen (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2018)
Previously, we proposed compressed sensing based synthetic transmit aperture (CS-STA) to improve the contrast and frame rate of STA while maintaining its spatial resolution in linear array by choosing uniform random matrix as the measurement matrix and transmitting the plane waves (PWs). In this paper, to extend CS-STA for phased array imaging and further improve its performance, we design four types of CS-STA implementations with different combinations of measurement matrices (i.e., uniform random and Hadamard matrices) and transmitted waves [i.e., PW and diverging wave (DW)]. Through simulations and phantom experiments with a 3 MHz, 64-element phased array, we find that type-IV CS-STA with the combination of a Hadamard matrix and DW outperforms the other three implementations including the previously proposed type-I CS-STA in terms of image quality and reconstruction time. Specifically, PW transmission produces visible discontinuity and the reconstruction time with uniform random matrix is about 100-fold longer than that with the Hadamard matrix. Compared with STA, with eightfold higher frame rate, type-IV CS-STA achieves 8.2 and 12.3 dB higher contrast-to-noise ratio and signal-to-noise ratio in the simulations, respectively. These improvements are slightly lower in the phantom experiments, which are 6.2 and 6.6 dB, respectively. In addition, CS-STA does not deteriorate the spatial resolution of STA, with the maximum deterioration being smaller than 1/8 wavelength. These results demonstrate that type-IV CS-STA can achieve phased array imaging with high image quality at high frame rate and may be beneficial to cardiac imaging.